The Active Role of Gifted Students in the Preparation and Evaluation of Individualized Programs - Gabrijelčič, Mojca; Željeznov Seničar, Maruška (Revija za elementarno izobraževanje, 2024)
The article highlights the importance of the active participation of gifted students in the process of preparation and evaluation of the Individualized Program (INDEP) based on their abilities, desires and needs. Through a qualitative comparative analysis of the content of three hundred individualized programs for gifted students, we found that the basic principle of involving gifted students in the content preparation and evaluation of the INDEP was taken into account. We found that the active role of gifted students, content adaptations in planning individualized programs and instructional challenges, general and specific objectives, and tutoring and support were partially addressed. Written goals in individualized programs do not reflect the individual goals of particular gifted students and are often worded the same for all gifted students in the same school.
Keywords: individualized program, giftedness, gifted students, active participation, evaluation